Healer (commissioned trade copy of earlier design) - Morris, Meheina, artist (Colorado State University. Libraries, 1999)
The sick person is in a hammock inside a house with thatched roof and vertical cane walls. Clothing is stored by hanging it from the rafters. As part of their healing practices, the healers are smoking pipes and burning cocoa bean incense in a sianala (brown clay brazier). The healer holds a wooden staff topped with a carved bird. Other power objects are clustered beneath the hammock, and plants and animals, which have spiritual powers, are nearby.
This item was part of an exhibition at the Avenir Museum of Design and Merchandising titled Kuna Molas: Sewn Stories and the Interplay of Tradition and Change, August 18, 2014-July 31, 2015.
Cotton; 3 layers (maroon, orange, red); reverse and direct appliqué, embroidery.
Keywords: Molas -- Panama; Appliqué -- Panama; Embroidery -- Panama